Inhibition of G9a Histone Methyltransferase Converts Bone Marrow Mesenchymal Stem Cells to Cardiac Competent Progenitors - Yang, Jinpu (Stem Cells Int, 2015)
The G9a histone methyltransferase inhibitor BIX01294 was examined for its ability to expand the cardiac capacity of bone marrow cells. Inhibition of G9a histone methyltransferase by gene specific knockdown or BIX01294 treatment was sufficient to induce expression of precardiac markers Mesp1 and brachyury in bone marrow cells. BIX01294 treatment also allowed bone marrow mesenchymal stem cells (MSCs) to express the cardiac transcription factors Nkx2.5, GATA4, and myocardin when subsequently exposed to the cardiogenic stimulating factor Wnt11. Incubation of BIX01294-treated MSCs with cardiac conditioned media provoked formation of phase bright cells that exhibited a morphology and molecular profile resembling similar cells that normally form from cultured atrial tissue. Subsequent aggregation and differentiation of BIX01294-induced, MSC-derived phase bright cells provoked their cardiomyogenesis. This latter outcome was indicated by their widespread expression of the primary sarcomeric proteins muscle α-actinin and titin. MSC-derived cultures that were not initially treated with BIX01294 exhibited neither a commensurate burst of phase bright cells nor stimulation of sarcomeric protein expression. Collectively, these data indicate that BIX01294 has utility as a pharmacological agent that could enhance the ability of an abundant and accessible stem cell population to regenerate new myocytes for cardiac repair.